American Dream Portrayal In 1930s American Society Through the Boys in the Boat (2023) - Rachman, Sarah; Jati, Ariya (Journal of English Language and Education, 2025)
This study examines how The Boys in the Boat (2023) represents the American Dream in 1930s American society through the portrayal of social and economic conditions.  Set during the Great Depression, the film depicts poverty, unemployment, and social pressure, illustrating the working class’s struggle to achieve success and foster nationalism through the 1936 Berlin Olympics. Using a qualitative descriptive method, the analysis covers both intrinsic and extrinsic elements. The findings show that the film highlights resilience, solidarity, and persistence among the lower class in facing adversity. Overall, it reflects the socio-political climate of 1930s America and presents the American Dream as a symbol of hope and revival amid crisis.